Development of Electronic Student Activity Sheet (E-LKM) Utilization of Used Cooking Oil for Chemistry Education Students - Ahmad Khairu Ramadhan; Maria Erna; Roza Linda (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to develop an electronic student activity sheet (E-LKM) utilization of used cooking oil for chemistry education students in entrepreneurship courses. This research is development research with the Plomp development model. The data obtained came from 6 validators (3 material experts and 3 media experts), 3 lecturers of entrepreneurship courses, and 30 students from three universities, namely Riau University, Sultan Syarif Kasim Riau State Islamic University, and Riau Islamic University. Data collection techniques are used in the form of interviews, documentation, and questionnaires. The data analysis technique is by calculating the percentage score of the validation assessment and user response. The results showed that the developed E-LKM met the very valid criteria with a percentage of 92.13% by material experts and 90.70% by media experts. The results of the responses of lecturers and students show that the developed E-LKM meets the very good criteria with a percentage of 82.93% by lecturers and meets the attractive criteria of 84.51% by students.